Summary: Poetic Edda - Vijūnas, Aurelijus (Scandinavistica Vilnensis, 2009)
The first complete translation of the Poetic Edda from Old Icelandic into Lithuanian, which contains both the mythological and heroic poems from the medieval Icelandic manuscript GKS 2365 4° (Codex Regius, isl. Konungsbók) and a number of Eddic poems from later manuscripts.   Pirmasis išsamus Poetinės Edos vertimas iš senosios islandų kalbos į lietuvių kalbą, į kurį įtrauktos mitologinės ir herojinės giesmės iš islandiško viduramžių rankraščio GKS 2365 4° (Codex Regius, isl. Konungsbók) bei kelios edinės giesmės iš vėlesnių rankraščių.
Keywords: Poetic Edda; translation into Lithuanian; Old Norse literature